(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
Last June Carlo Smuraglia, a very prestigious member of the editorial committee of this Review, passed away. His long life was dedicated to law and justice. In this article, his figure and his biography are retraced to highlight and frame the great contribution he made to the fight against the mafia in a decisive period at the end of the last century. He gave it both in the theoretical-juridical support of the Rognoni-La Torre law and in the creation of an important daily jurisprudence, made up of regulatory and administrative principles and instruments, and in the promotion of knowledge of the mafia phenomenon in a Northern Italy distracted and perennially tempted by removal. Exemplary was also his commitment in defense of the Constitution and in support of the memory of the victims.